Studi Hidrogeokimia di Eks-TPA Jelekong dan Perbandingannya TPA Sarimukti - Muhammad Iqbal Musthofa; Yundhera Danazahra; Yaumun Nurul Chotimah; Hanifa Octaviani; Irwan Iskandar (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The Jelekong landfill was a temporary landfill site following a landslide at the Leuwigajah landfill. TPA Jelekong was officially closed at the end of 2005 because it was no longer able to accommodate the increasing volume of waste. However, the impact of activities from the former landfill still has the potential to pollute the environment, especially groundwater sources. The research aimed to identify the physical and chemical parameters of water in the Jelekong ex-landfill case study area and the surrounding area, and to compare the physical and chemical parameters of water between the Jelekong ex-landfill and the landfill that is still operating (Sarimukti landfill). Data were obtained from 4 water sample points and tested using several test methods, namely Inductively Coupled Plasma Mass Spectrometry (ICP-MS), Ion Chromatography (IC), alkalinity, and stable water isotopes. The results showed that the physical characteristics of the Jelekong area generally have a neutral pH with one point having an alkaline pH (JL-02) due to interaction with andesite lithology and the highest DO concentration at point JL-02. While the Sarimukti landfill has a pH value of 7.89-8.27 indicating the result of high bicarbonate concentrations, the TDS value of 15700-18200 ppm indicates the large number of ions and solutes derived from organic and inorganic waste. Piper diagrams show two water facies in the Jelekong area, Ca-HCO3 and Na-HCO3. Sample JL-03 indicates a mixture with landfill leachate due to high Cl and SO4 concentrations. Sample JL-01 still indicates leachate because when compared to the sarimukti sample, the Cl and SO4 concentrations are still quite high indicating a result of both organic and inorganic waste. Stable isotope test results indicated that the water was derived from local precipitation.